How Commercially Available Virtual Reality–Based Interventions Are Delivered and Reported in Gait, Posture, and Balance Rehabilitation: A Systematic Review. Issue 10 (16th July 2020) - Weber, Heather; Barr, Christopher; Gough, Claire; van den Berg, Maayken
Abstract: Objective: Virtual reality (VR) technologies are increasingly used in physical rehabilitation; however, it is unclear how VR interventions are being delivered, and, in particular, the role of the therapist remains unknown. The purpose of this study was to systematically evaluate how commercially available VR technologies are being implemented in gait, posture, and balance rehabilitation, including justification, content, procedures, and dosage of the intervention and details of the therapist role. Methods: Five databases were searched between 2008 and 2018. Supervised interventional trials with >10 adult participants using commercially available VR technologies to address mobility limitations were independently selected by 2 authors. One author extracted reported intervention characteristics into a predesigned table and assessed methodological quality, which was independently verified by a second author. A total of 29 studies were included. Results: Generally, minimal clinical reasoning was provided to justify technology or activity selection, with recreational systems and games used most commonly (n = 25). All but 1 study used a single interventional technology. When explicitly described, the intervention was delivered by a physical therapist (n = 14), a therapist assistant (n = 2), both (n = 1), or an occupational therapist (n = 1). Most studies reported supervision (n = 12) and safeguarding (n = 8) as key therapist roles, with detail of therapist feedback less frequently reported (n = 4). Therapist involvement in program selection, tailoring, and progression was poorly described. Conclusion: Intervention protocols of VR rehabilitation studies are incompletely described and generally lack detail on clinical rationale for technology and activity selection and on the therapist role in intervention design and delivery, hindering replication and translation of research into clinical practice. Future studies utilizing commercially available VR technologies should report all aspects of intervention design and delivery and consider protocols that allow therapists to exercise clinical autonomy in intervention delivery. Impact Statement: The findings of this systematic review have highlighted that VR rehabilitation interventions targeting gait, posture, and balance are primarily delivered by physical therapists, whose most reported role was supervision and safeguarding. There was an absence of detail regarding complex clinical skills, such as tailoring of the intervention and reasoning for the choice of technology and activity. This uncertainty around the role of the therapist as an active ingredient in VR-based rehabilitation hinders the development of implementation guidelines. To inform the optimal involvement of therapists in VR rehabilitation, it is essential that future studies report on all aspects of VR intervention design and delivery.